Visualizing Changes in Cytosolic-Free Ca2+ during the Response of Stomatal Guard Cells to Abscisic Acid. - McAinsh, MR (1992)
In this paper, we report the results of a detailed investigation into abscisic acid (ABA)[mdash]stimulated elevations of guard cell cytosolic-free Ca2+ ([Ca2+]cyt). Fluorescence ratio photometry and ratio imaging techniques were used to investigate this phenomenon. Guard cells of open and closed (opened to 10 to 12 [mu]m before treatment with ABA) stomata were microinjected with the fluorescent Ca2+ indicator Indo-1. Resting [Ca2+]cyt ranged from 50 to 350 nM. ABA (100 nM) stimulated an increase in [Ca2+]cyt in 68 and 81% of guard cells microinjected in the open and closed configuration, respectively. All stomata were observed to close in response to ABA. Increases ranged from 100 to 750 nM above the resting concentration and were arbitrarily grouped into five "classes." ABA-stimulated increases in [Ca2+]cyt were not uniformly distributed across the cytosol of guard cells. Rapid transient increases in [Ca2+]cyt were also observed in the guard cells of stomata microinjected in the closed configuration. We concluded that the ABA-induced turgor loss in guard cells is a Ca2+-dependent process.